دەقئاوێزانى ئایینى لە شیعرى مەولەوى تاوەگۆزییدا - طه, پ.ی.د.عدنان عبدالرحمن (Sulaimani Journal for Humanities, 2023)
The research (religious intertextuality in the poems of Mawlawi Taguzi) is a scientific effort based on the theory of intertextuality in order to reveal and open those symbols that Mawlawi the poet took from the sources of Quranic verses, hadiths and Islamic sciences in religious intertextuality. It is clear that the poet in question grew up in religious centers and mosques and in the service of Quranic verses and hadiths. We can see the great influence of that religious environment on him, and this was the strongest reason for Mawlawi to dedicate a large part of his poems to religious themes. This research consists of a summary, an introduction, two chapters, results, references, and a research summary in both Arabic and English
Keywords: Keywords Molloy; religious intertextuality